CXCR4 Is Required by a Nonprimate Lentivirus: Heterologous Expression of Feline Immunodeficiency Virus in Human, Rodent, and Feline Cells - Poeschla, Eric M. (American Society for Microbiology, 1998)
A heterologous feline immunodeficiency virus (FIV) expression system permitted high-level expression of FIV proteins and efficient production of infectious FIV in human cells. These results identify the FIV U3 element as the sole restriction to the productive phase of replication in nonfeline cells. Heterologous FIV expression in a variety of human cell lines resulted in profuse syncytial lysis that was FIV env specific, CD4 independent, and restricted to cells that express CXCR4, the coreceptor for T-cell-line-adapted strains of human immunodeficiency virus. Stable expression of human CXCR4 in CXCR4-negative human and rodent cell lines resulted in extensive FIV Env-mediated, CXCR4-dependent cell fusion and infection. In feline cells, stable overexpression of human CXCR4 resulted in increased FIV infectivity and marked syncytium formation during FIV replication or after infection with FIV Env-expressing vectors. The use of CXCR4 is a fundamental feature of lentivirus biology independent of CD4 and a shared cellular link to infection and cytopathicity for distantly related lentiviruses that cause AIDS. Their conserved use implicates chemokine receptors as primordial lentivirus receptors.